On Classic Ground : Picasso, Léger, de Chirico and the New Classicism 1910-1930 - Cowling, Elizabeth; Mundy, Jennifer (London : Tate Gallery, 1990)
Andreu, Mariano ; Bernard, Joseph ; Bonnard, Pierre ; Bourdell, Emile Antoine ; Braque, Georges ; Campigli, Massimo ; Carrà, Carlo ; Casonovas, Enric ; Casorati, Felice ; Cézanne, Paul ; Clara, José ; Dali, Salvador ; Derain, André ; Gonzalez, Julio ; Maillol, Aristide ; etc.
On Classic Ground : Picasso, Léger, de Chirico and the New Classicism 1910-1930, The Tate Gallery, London, 6 June - 2 September 1990
boek
Keywords: Picasso, Pablo; Léger, Fernand; de Chirico, Giorgio